Active rejection control for unknown harmonic disturbances of the transverse deflection of steel strips with control input, system output, sensor output, and disturbance input at different positions. (December 2018) - Saxinger, Martin; Marko, Lukas; Steinboeck, Andreas; Kugi, Andreas
Abstract: In hot-dip galvanizing lines for steel strips, it is important to ensure a homogeneous zinc layer thickness. For this, vibrations of the strip at the gas wiping dies, where excess liquid zinc is blown off, must be suppressed. These vibrations typically exhibit a dominant sinusoidal shape and the excitation process, the frequency, the amplitude, and the phase are generally unknown. In modern plants, electromagnetic actuators are employed to enable a contactless vibration and shape control of the steel strip. Vibration control of flexible structures is well established in literature. However, in the considered application the disturbance (source of periodic excitation), the control input (force of electromagnetic actuators), the sensor output (strip displacement) and the desired system output (strip displacement at the gas wiping dies) are all located at different positions along the strip, which makes the overall control task quite challenging. In this paper, a control concept consisting of a linear quadratic regulator combined with a disturbance feedforward concept based on the theory of invariant manifolds and an Extended Kalman Filter is developed. The proposed control strategy is successfully tested on an experimental test rig for different scenarios.